Pengujian Kadar Formalin pada Ikan Asin di Pasar Tradisional Kota Sorong menggunakan Spektrofotometer UV-Visible - Rattagi, Maria Ikawati Nantu (Universitas Muhammadiyah Gresik, 2025)
Most fish processing in Indonesia is still done using the old methods, including fermentation, smoking, grilling and salting. . Formaldehyde is basically a preservative that should not be used in food, this is because it will be dangerous for anyone who eats it. The aim of this research was to determine whether salted fish in the Sorong City traditional market was detected to be mixed with formalin and the levels of formalin contained in salted fish using a UV-Visible Spectrophotometer. This research is an experimental design research which includes qualitative tests and quantitative tests with salted sea bream and salted white snapper as research objects. The results of the research were that there were 2 positive samples from the 12 samples tested. Samples with code (K3) and code (K4) have a sign that the color changes to purple after adding chromatogenic acid as a reagent. The total levels contained in salted fish, namely the salted fish sample with the code (K3) has a total level of 0,1397% and for salted fish with the code (K4) it has a total level of 0,1152% with the wavelength measured, namely 582 nm.